2000
DOI: 10.2500/105065800781692886
|View full text |Cite
|
Sign up to set email alerts
|

Endonasal Endoscopic Marsupialization of Paranasal Sinus Mucoceles

Abstract: Paranasal sinus mucoceles are relatively common in Japan, especially after prior Caldwell-Luc surgery. Recently developed endonasal endoscopic approaches were used for the drainage and marsupialization of mucoceles. We present the surgical treatment of 97 patients with mucoceles, including 68 maxillary, 13 ethmoid, nine frontal, seven sphenoid, eight frontoethmoid, and one sphenoethmoid sinuses. Six patients with maxillary mucoceles were operated via a sublabial incision. For frontal mucoceles, four patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
4

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 32 publications
3
32
0
4
Order By: Relevance
“…Several etiological factors are identified such as cystic fibrosis [1,2,5]. Imaging evaluation includes CT-scan (and sometimes MRI) and surgical management is now unanimously performed by endoscopic approach [1,[6][7][8][9]. The goal of this retrospective study is on one hand to analyze the local and general etiological factors, and on the other hand to evaluate the results of the endonasal marsupialization.…”
Section: Introductionmentioning
confidence: 99%
“…Several etiological factors are identified such as cystic fibrosis [1,2,5]. Imaging evaluation includes CT-scan (and sometimes MRI) and surgical management is now unanimously performed by endoscopic approach [1,[6][7][8][9]. The goal of this retrospective study is on one hand to analyze the local and general etiological factors, and on the other hand to evaluate the results of the endonasal marsupialization.…”
Section: Introductionmentioning
confidence: 99%
“…1 Over the past decade, intranasal drainage and marsupialization of mucocoeles using ESS has emerged as definitive management, with minimal morbidity and a low recurrence rate. [3][4][5][6][7][8][9][10][11][12] With the advent of more advanced instrumentation, refined surgical techniques, and intraoperative imaging, even the more technically challenging frontal mucocoeles can be approached endoscopically.…”
Section: Introductionmentioning
confidence: 99%
“…All the patients had plain radiograph while only 11 had computerized axial tomography scanning (CT Scan). This revealed localized opacity in the maxillary antrum in (7), frontal sinus (4 ), multiple sinus involvement in ( 21), destruction of bony walls of the sinuses (16) and destruction of the sphenoid and cribriform plate (6) and lamina papyracea (5) (Fig 3). Using the Mackay and Lund 5 staging of nasal polyps, all the polyps were stage 3.…”
Section: Resultsmentioning
confidence: 99%
“…We had recurrence following the Lynch -Howarth (frontoethmoidectomy) procedure for resection of mucocoele. In a report of 48 mucocoeles, 20 treated by an entirely endoscopic approach and 28 by combined external and endoscopy, Lund [2] reported no recurrence with endoscopy and 3 recurrences with the combined group, Ikeda et al [6] reported no recurrence in a series of 97 patients with mucocoele treated with endoscopy and external approach after 36-84 month follow-up period. Kennedy et al [9] reported endoscopic marsupialization in 18 cases without recurrence.…”
Section: Discussionmentioning
confidence: 99%